Impact of intermittent fasting on human health: an extended review of metabolic cascades. Issue 1 (1st January 2018) - Ahmed, Aftab; Saeed, Farhan; Arshad, Muhammad Umair; Afzaal, Muhammad; Imran, Ali; Ali, Shinawar Waseem; Niaz, Bushra; Ahmad, Awais; Imran, Muhammad
ABSTRACT: In the present scenario, the literature is available regarding different challenging matters; however, some horizons still need to be elucidated and "Intermittent Fasting" is one of such examples. For millennia, several scientific interventions were carried out to probe the effect of fasting on human metabolic activities. There are three common strategies of fasting like caloric restriction (CR), dietary restriction (DR) and Intermittent fasting (IF) but IF has emerged as an avenue of potential benefit and wellbeing of the consumer. Intermittent fasting is the prehistoric surreptitious of human health as this powerful habit has been virtually forgotten. Nowadays, numerous researchers are reviving this dietary intervention. It carries enormous consequences such as increased energy, weight loss, and reversal of type-II diabetes. Moreover, it encloses the important evidence validating the health claims of IF with special reference to cancer, coronary heart diseases, biomarkers of oxidative stress and insulin sensitivity. Furthermore, the impact of intermittent fasting on human health based upon metabolic case studies are the limelight of the current manuscript. Conclusively, Intermittent fasting (IF) is the most appropriate tactic for its capability to ameliorate different lifestyle related disorders for instance; diabetes, cardiovascular disorder, cancer, antioxidant stress, and renal diseases.